Linking Intensive Care Unit functional scales to the International Classification of Functioning: proposal of a new assessment approach - Juliana S. F. dos Santos; Gabriely A. G. Silva; Nubia M. F. V. Lima; Lucien P. Gualdi; Diego de S. Dantas; Íllia N. D. F. Lima (BMC, 2023)
Abstract Background There are several tools to assess functional and physical status in critical ill patients. These tools can guide rehabilitation strategies in Intensive care units (ICU). However, they are not standardized, and this can compromise their applicability. The aim of the study is to identify common contents between International Classification of Functioning, Disability and Health (ICF) and Medical Research Council sum score (MRC-ss), Functional Status Score for the ICU (FSS-ICU), and Physical Function in ICU Test-scored (PFIT-s). As well as to propose a new assessment approach based on the ICF to ICU patients. Methods Pilot cross-sectional study. ICU in-patients, both genders, aged between 50 and 75 years were assessed with MRC-ss, FSS-ICU, PFIT-s and the linking rules used were proposed by Cieza et al. The inter-rater agreement for the linking process was performed using the Kappa coefficient. Results The ICF categories identified in the tools covered a total of 14 items. Common contents were identified in 13 of the 14 and two were related to body functions, six to body structures and five to activities and participation. The inter-rater agreement was considered substantial for the linking of MRC-ss (k = 0.665) and PFIT-s (k = 0.749) to the ICF, and almost perfect for the FSS-ICU (k = 0.832). Conclusions This study synthesizes and categorizes commonly used tools and presents a new proposal based on the ICF to guide future studies. The proposed model combines the ICF with the contents of the most relevant instruments used in critical care.